2015
DOI: 10.1680/geot.14.t.016
|View full text |Cite
|
Sign up to set email alerts
|

A fractal model for volume change dependency of the water retention curve

Abstract: A fractal-based approach for volume change dependency of the water retention curve in a deformable unsaturated soil is presented. Conservation laws of solid mass and solid surface for uncrushable grains and Eshelby's classical theory for load-deformation of a single elastic ellipsoidal void embedded in an infinite isotropic elastic matrix are exploited to derive analytical expressions for the evolution of pore size distribution fractal dimension, air entry suction and hence water retention curve with void rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Numerous studies have shown that the radius and tortuosity of pores have directly affected permeability of porous media. , Also, a fractal theory could well consider these parameters and explain the flow behavior of gas in porous media. ,, Therefore, along with dynamic fractal dimensions and the critical capillary radius quantified in Sections and , the apparent permeability model for coal under the coupling actions of stress and water has been established.…”
Section: Establishment Of the Apparent Permeability Modelmentioning
confidence: 99%
“…Numerous studies have shown that the radius and tortuosity of pores have directly affected permeability of porous media. , Also, a fractal theory could well consider these parameters and explain the flow behavior of gas in porous media. ,, Therefore, along with dynamic fractal dimensions and the critical capillary radius quantified in Sections and , the apparent permeability model for coal under the coupling actions of stress and water has been established.…”
Section: Establishment Of the Apparent Permeability Modelmentioning
confidence: 99%
“…The experimental results of saturated tests are evaluated based on the effective stress principle (σ′v = σvuw). Simplified methods for calculation of unsaturated effective stress based on the single effective stress approach can be found in Khoshghalb and Khalili (2013) and Khoshghalb et al (2015). However, in this work, the experimental results of unsaturated tests are evaluated based on the vertical net stress (σvnet = σvua).…”
Section: Test Materials and Apparatusmentioning
confidence: 99%
“…A critical step in modelling the behaviour of unsaturated soils is the determination of the soil water retention capacity at various suctions and hydraulic loading conditions (ie, main drying, main wetting, or suction reversals) at a given density state. A number of models are proposed to take account of the volume change dependency of the SWRC, eg, references herein . In this study, a void ratio–dependent SWRC similar to that presented in Pasha et al is adopted.…”
Section: Governing Equationsmentioning
confidence: 99%
“…A number of models are proposed to take account of the volume change dependency of the SWRC, eg, references herein. 82,[87][88][89][90] In this study, a void ratio-dependent SWRC similar to that presented in Pasha et al 82 is adopted. The salient feature of this model is that while it captures the volume change dependency of all branches of the SWRC (ie, main drying, main wetting, and scanning), it does not introduce any additional parameter into the formulation.…”
Section: Void Ratio-dependent Water Retention Curvementioning
confidence: 99%